1996
DOI: 10.1111/j.1399-3054.1996.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and oxygen stress in Spirulina platensis (cyanobacteria) grown outdoors in tubular reactors

Abstract: As the effects of light and oxygen stress in algae on mass culture has not been intensively studied, we investigated them in Spirulina platensis under outdoor conditions in controlled tubular reactors where the respective roles of each stress can be distinguished. It was observed that exposure of this cyanobacterium at two oxygen concentrations (ca 20 and 53 mg 1−1) caused very little change in the ratio between variable and maximum fluorescence (Fv/Fm) during the day even when the culture was grown at higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…The decrease in quantum yield of S. platensis (Vonshak et al 1996) and C. sorokiniana (Ugwu et al 2007) proved to be accompanied by a gradual decrease in the ratio between variable and maximum fluorescence. This indicates that higher oxygen concentrations cause destruction of the chlorophyll via photo-oxidative inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in quantum yield of S. platensis (Vonshak et al 1996) and C. sorokiniana (Ugwu et al 2007) proved to be accompanied by a gradual decrease in the ratio between variable and maximum fluorescence. This indicates that higher oxygen concentrations cause destruction of the chlorophyll via photo-oxidative inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table , a DO of 55‐60 mg L –1 was reported for S. platenesis culture in a bench TPBR of 50 L made of 10 parallel Pyrex tubes with a length of 2 m and a diameter of 0.0485 m. Cultivation was carried out outdoor in water baths controlled at 35 o C. A biomass concentration of 1.4 g L –1 at a productivity of 0.417 g L –1 d –1 was achieved. The high DO levels observed within these short tubes of 2 m highlight the need of designing efficient deoxygenation mechanisms for TPBR since oxygen accumulation would increase with the increase of tube length if other conditions are the same.…”
Section: Oxygen Evolutionmentioning
confidence: 99%
“…Furthermore, it was observed that many algal species cannot withstand the exposure of 2‐3 hours to oxygen levels much above air saturation . Observation on the effect of extended exposure to oxygen on the growth of Spirulina indicated that irreversible damage took place after 30–32 h of exposure to the concentration of 36 mg L –1 oxygen . Moreover, a high degree of cell lysis and death of Chlorella sorokiniana was observed when DO exceeded 200% of air saturation (13 mg O 2 L –1 at 38°C) .…”
Section: Oxygen Evolutionmentioning
confidence: 99%
“…To compensate for these effects, algae and higher plants can decrease the photosynthetic rate to reduce damage to the photosynthetic proteins (Osmond, ). These phenomena have been observed both in open (Moheimani and Borowitzka, ) and closed algal production systems (Molina et al, ; Pulz, ; Vonshak et al, ), where the inhibitory effects were commonly noted at dissolved oxygen levels approaching 36 mg L −1 .…”
Section: Introductionmentioning
confidence: 92%